2020
DOI: 10.1186/s12992-020-00585-0
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of global health capacity building initiatives in low-to middle-income countries in the Middle East and North Africa region

Abstract: Introduction Low-and Middle-Income Countries (LMICs) in the Middle East and North Africa (MENA) region are facing increasing global health challenges with a reduced ability to manage them. Global Health Capacity Building (GHCB) initiatives have the potential to improve health workforce performance and health outcomes, however little is known about the GHCB topics and approaches implemented in this region. This is the first systematic review of GHCB initiatives among LMICs in the MENA region. Methods An academ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

5
5

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 58 publications
1
20
0
Order By: Relevance
“…In light of this, an increase in screening efforts and referral mechanisms to PHCs and other health facilities is highly needed to improve access to mental health services and to reduce depression symptoms. One recommended way to do that is through task shifting, by conducting more capacity building initiatives that train non-specialized community health workers to deliver basic mental health services to their communities and to conduct referrals [55,56]. According to a recent national facility assessment, almost 32% of PHCs in Lebanon are currently delivering mental health services following the mhGAP training, and almost 50% of them cover rural areas [57], where most refugees reside.…”
Section: Recommendations and Implicationsmentioning
confidence: 99%
“…In light of this, an increase in screening efforts and referral mechanisms to PHCs and other health facilities is highly needed to improve access to mental health services and to reduce depression symptoms. One recommended way to do that is through task shifting, by conducting more capacity building initiatives that train non-specialized community health workers to deliver basic mental health services to their communities and to conduct referrals [55,56]. According to a recent national facility assessment, almost 32% of PHCs in Lebanon are currently delivering mental health services following the mhGAP training, and almost 50% of them cover rural areas [57], where most refugees reside.…”
Section: Recommendations and Implicationsmentioning
confidence: 99%
“…While evidence suggests that global health capacity building initiatives are beneficial, little is known about their success in the MENA region and especially regarding women's health in refugee populations, given the scarcity of case studies on this issue [13]. In fact, based on a recent systematic review, there is an increasing need for data on the effectiveness of capacity building programs that target CHWs, given their potential to provide non-specialized and essential services in low-resource settings [15].…”
Section: Introductionmentioning
confidence: 99%
“…With regard to the weaknesses, most of the reviewed papers reflected short-term and generic descriptions of a given intervention with little to no report on short- or long-term evaluations or impact assessments. Although the political and social instability throughout FCASs prompts the implementation of short-term interventions, a follow-up strategy for assessing the feasibility, benefits, and impacts of such interventions is crucial as it informs future directions and contributes to the sustainability of capacity building projects [ 92 , 93 ]. The problem of sustainability for research in FCASs is primarily a matter of resources, as demonstrated by the major disparity in spending on research between HIC and LMICs.…”
Section: Discussionmentioning
confidence: 99%